Krčenje Triglavskega ledenika v luči osončenosti - Gabrovec, Matej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
In the discussions about climate change, the shrinking of glaciers was often presented as an indicator of temperature changes. Yet, for the melting of glaciers the solar radiance exposure is more important than the air temperature. Our interest in the present article is focused on the differences between individual years at the same location, i.e. on the Triglav glacier. The data on radiance exposure in the glacier melting season were compared with the concurrent shrinking of the glacier and, accordingly, an assessment was made about the significance of radiance exposure as to the other meteorological factors.
Keywords: glaciologija; ledeniki; meritve; podnebne spremembe; sončno obsevanje; temperatura; Triglavski ledenik